(untitled) (Journal of the College of Basic Education, 2025)
In this paper the stylistic variations between some chosen western and Arab middle-east famous presidential eulogies of two languages and cultures are investigated. The languages in question are namely English as represented by the American memorial speeches and Arabic as represented by Arab presidential memorial speeches. As an analytical model, Leech and Short (2007) is selected as an empirical reference of stylistic analysis where the categories to be applied on the texts under analysis are those, the relevant lexical as well as the figurative ones featuring the commemorative speeches. Frequency-based statistics are also conducted following the categories in the adopted model. The paper has come up with several conclusions, among which are: stylistic choices are highly controlled by the cultural context. In the case of American eulogies, the speeches have focus on clarity and personal legacy. It is also noted that Arabic eulogies represent a rich poetry tradition.